2005
DOI: 10.1097/01.ico.0000148288.53323.b2
|View full text |Cite
|
Sign up to set email alerts
|

A Morphologic Study of Fuchs Dystrophy and Bullous Keratopathy

Abstract: Histopathologic changes in the corneal stroma and keratocytes occur in Fuchs dystrophy. Secondary lipid keratopathy ensues and may contribute to corneal haze. A higher proportion of keratocytes in Fuchs dystrophy have granular deposit than in bullous keratopathy. That a high proportion of keratocytes had degenerative changes in both Fuchs dystrophy and bullous keratopathy suggests that keratocytes may degenerate secondary to altered stromal microenvironment because of endothelial cell loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 37 publications
2
45
0
Order By: Relevance
“…Ex vivo studies have confirmed decreased endothelial density in FECD (Davies et al, 1997) and have also shown that the endothelium is significantly thinner than normal, sometimes as thin as 0.06 mm, especially in areas overlying guttae (Bourne et al, 1982;Kayes and Holmberg, 1964;Yuen et al, 2005). In one ultrastructural study of FECD, endothelial nuclei were located in "valleys" between guttae and cells were extremely thin over the guttae.…”
Section: Hernandezmentioning
confidence: 86%
See 1 more Smart Citation
“…Ex vivo studies have confirmed decreased endothelial density in FECD (Davies et al, 1997) and have also shown that the endothelium is significantly thinner than normal, sometimes as thin as 0.06 mm, especially in areas overlying guttae (Bourne et al, 1982;Kayes and Holmberg, 1964;Yuen et al, 2005). In one ultrastructural study of FECD, endothelial nuclei were located in "valleys" between guttae and cells were extremely thin over the guttae.…”
Section: Hernandezmentioning
confidence: 86%
“…The cells have little cytoplasm but still maintain a smooth posterior surface and desmosomes are still present (Kayes and Holmberg, 1964). However, marked vacuolization and melanin pigment have been observed between and within cells (Kayes and Holmberg, 1964;Naumann and SchlotzerSchrehardt, 2000;Yuen et al, 2005). No inflammatory cell infiltration or blood vessels were observed at the level of the endothelium (Yuen et al, 2005).…”
Section: Hernandezmentioning
confidence: 94%
“…[10][11][12] In the first year following Descemet's membrane endothelial keratoplasty, Descemet's stripping automated endothelial keratoplasty, and penetrating keratoplasty, endothelial cell losses have been reported as 35%, 11 14.9%, 12 and 16.5%, 10 respectively. By the third postoperative year, endothelial cell losses will have increased to approximately 47%, 11 29.7%, 13,14 and 55%, 10 respectively. The progression of endothelial cell loss may eventually lead to graft failure and repeat graft surgeries in some patients.…”
mentioning
confidence: 99%
“…25 Various causative factors such as excessive phacoemulsification energy 26 and mechanical trauma 27 to the corneal endothelium during cataract extraction surgery have been implicated in causing stress-induced apoptosis of CECs. 28 Although PBK is characterized by diffuse damage to the corneal endothelial layer, 29 a peripheral rim of healthy CECs and DM is usually retained in corneas affected by FED. 22 As such, it has been postulated that this reservoir of healthy CECs in FED corneas can potentially be exploited to repopulate the centrally diseased corneal endothelium either by migration or proliferation, on exposure to externally applied stimulants.…”
mentioning
confidence: 99%
“…As commented above, a preexisting lowgrade inflammation at the corneo-scleral limbus or a local cellular defect may be responsible for the lipid deposition. Yuen et al recently found a high percentage of lipid keratopathy in avascular corneas with Fuchs dystrophy or bullous keratopathy, and suggested that lipid deposition can be related to keratocyte degeneration [10]. Also recently, Loeffler and Seifert [11] described a patient with severe idiopathic bilateral opacification of the cornea with bulging to the anterior cornea, because of deposition of intracellular and extracellular lipids.…”
Section: Discussionmentioning
confidence: 96%